Self-regulated reionization - Iliev, Ilian T.; Mellema, Garrelt; Shapiro, Paul R.; Pen, Ue-Li (Monthly notices of the Royal Astronomical Society, 2007)
Recently, we have presented the first, truly large-scale radiative transfer simulations of inhomogeneous cosmic reionization which resolve all the possible halo sources down to the dwarf galaxy mass range, M≳ 109 M⊙, in a comoving volume (100 h−1 Mpc)3. This is large enough to sample the global mean history, geometry and statistical properties of reionization fairly and accurately for the first time. Here we present new simulations which extend the source halo mass range downward to 108 M⊙, to capture the full range of halo masses thought to be primarily responsible for reionization by their star formation following atomic hydrogen radiative cooling and gravitational collapse. Haloes below about 109 M⊙, however, are subject to Jeans-mass filtering in the ionized regions, which suppresses their baryonic content and their ability to release ionizing radiation. By including these smaller mass haloes but accounting for their suppression, too, we find that reionization is ‘self-regulating’, as follows. As the mean ionized fraction rises, so does the fraction of the volume within which suppression occurs. Hence, the degree of suppression is related to the mean ionized fraction. Since low-mass haloes with high efficiency (i.e. high emissivity) achieve a given mean ionized fraction earlier than do those with low efficiency, Jeans-mass filtering compensates for the difference in the emissivity of the suppressible haloes in these two cases. As a result, in the presence of lower mass source haloes, reionization begins earlier, but the later stages of reionization and the time of overlap are dictated by the efficiency of the higher mass haloes, independent of the efficiency of the suppressible, lower mass haloes. Hence, while the lower mass haloes do not alter the overlap redshift, zov, they serve to boost the electron-scattering optical depth of the universe, τes. This may explain why observations of quasar absorption spectra at high redshift find that reionization ended late (zov < 7), while cosmic microwave background polarization measurements report a large enough τes that reionization must have begun much earlier (z > 11). We present results for the Lambda cold dark matter universe with cosmological parameters from both 1- and 3-yr data releases of Wilkinson Microwave Anisotropy Probe. Reionization histories consistent with current constraints on zov and τes are shown to be achievable with standard stellar sources in haloes above 108 M⊙. Neither minihaloes nor exotic sources are required, and the phenomenon of ‘double reionization’ previously suggested does not occur.